The effect of trans-resveratrol on post-stroke depression via regulation of hypothalamus–pituitary–adrenal axis. (October 2015) - Pang, Cong; Cao, Liang; Wu, Fan; Wang, Li; Wang, Gang; Yu, Yingcong; Zhang, Meixi; Chen, Lichao; Wang, Weijie; Lv, Weihong; Chen, Ling; Zhu, Jiejin; et al.
Abstract: Post-stroke depression (PSD) occurs about 40% among all stroke survivors, but the effective pharmacotherapy is inadequately understood. The present study investigated the effects of a natural polyphenol trans -resveratrol (RES) on behavioral changes after middle cerebral artery occlusion (MCAO) and examined what its molecular targets may be. RES was shown to decrease the infarct size and neurological scores after MCAO, suggesting the amelioration of brain damage and motor activity. RES also reversed the depressive-like behaviors 13 days after MCAO, both in the forced swimming and sucrose consumption tests. Moreover, MCAO-induced series abnormalities related to depressive-like behaviors, such as an abnormal adrenal gland weight to body weight ratio, an increased expression of the corticotropin-releasing factor (CRF) in the frontal cortex, hippocampus and hypothalamus, the differential expression of glucocorticoid receptor (GR) in these three brain regions, and a decreased brain-derived neurotrophic factor (BDNF) level, were ameliorated after treatment with increasing doses of RES at 10, 20 and 40 mg/kg via gavage. These findings provide compelling evidence that RES protects the brain against focal cerebral ischemia-induced injury, but most of all is its antidepressant-like effect on PSD, which might at least in part be mediated by regulation of hypothalamus–pituitary–adrenal axis function. Highlights: We firstly report the effects of trans -resveratrol on post-stroke depression (PSD). We found that trans -resveratrol protects neurons against brain ischemic injury. The effects may be involved in modulation of PSD-related HPA axis dysfunction. The results provide theoretical support for resveratrol in the treatment of PSD.